The Role of the Manpower Office of Balikpapan City in Providing Legal Protection for Workers with Disabilities - Achmad Kemal K (Punggawa Law Review, 2026)
Legal protection for workers with disabilities is a fundamental aspect of equality, human dignity, and substantive access to decent work. In Balikpapan City, the realization of this protection depends on the institutional capacity of the Manpower Office to translate national disability-employment obligations into effective local administrative practice. This article examines the role of the Manpower Office of Balikpapan City in protecting workers with disabilities through inclusive employment policy, job-placement mediation, capacity building, quota-compliance monitoring, reasonable-accommodation guidance, and industrial-relations protection. This study applies a normative juridical method with statutory and conceptual approaches. The statutory approach is used to examine Law Number 8 of 2016 on Persons with Disabilities and Government Regulation Number 60 of 2020 on Disability Service Units in the Employment Sector, while the conceptual approach is used to analyse legal protection, substantive equality, reasonable accommodation, and inclusive employment governance. The article argues that formal legal recognition is insufficient without integrated disability labour data, accessible recruitment procedures, employer technical assistance, post-placement monitoring, and disability-sensitive complaint mechanisms. Strengthening the Disability Service Unit within the Manpower Office is therefore essential to ensure that workers with disabilities are protected not only formally, but also substantively within Balikpapan’s labour market.